The anatomy of the infrarenal lumbar splanchnic nerves in human cadavers: implications for retroperitoneal nerve‐sparing surgery. Issue 1 (21st November 2017) - Beveridge, Tyler S.; Fournier, Dale E.; Groh, Adam M.R.; Johnson, Marjorie; Power, Nicholas E.; Allman, Brian L.
Abstract: Injury to the nerves of the aortic‐ and superior hypogastric plexuses during retroperitoneal surgery often results in significant post‐operative complications, including retrograde ejaculation and/or loss of seminal emission in males. Although previous characterizations of these plexuses have done well to provide a basis for understanding the typical anatomy, additional research into the common variations of these plexuses could further optimize nerve‐sparing techniques for retroperitoneal surgery. To achieve this, the present study aimed to document the prevalence and positional variability of the infrarenal lumbar splanchnic nerves (LSNs) through gross dissection of 26 human cadavers. In almost all cases, two LSNs were observed joining each side of the aortic plexus, with 48% (left) and 33% (right) of specimens also exhibiting a third joining inferior to the left renal vein. As expected, the position of the LSNs varied greatly between specimens. That said, the vast majority (98%) of LSNs joining the aortic plexus were found to originate from the lumbar sympathetic trunk above the level of the inferior mesenteric artery. It was also found that, within specimens, adjacent LSNs often coursed in parallel. In addition to these nerves, 85% of specimens also demonstrated retroaortic LSN(s) that were angled more inferior compared with the other LSNs ( P  < 0.05), and exhibited a unique course between the aorta/common iliac arteries and the left common iliac vein before joining the superior hypogastric plexus below the aortic bifurcation. These findings may have significant implications for surgeons attempting nerve‐sparing procedures of the sympathetic nerves in the infrarenal retroperitoneum such as retroperitoneal lymphadenectomies. We anticipate that the collective findings of the current study will help improve such retroperitoneal nerve‐sparing surgical procedures, which may assist in preserving male ejaculatory function post‐operatively.